2018
DOI: 10.1093/femspd/fty056
|View full text |Cite
|
Sign up to set email alerts
|

Can the route of Toxoplasma gondii infection affect the ophthalmic outcomes?

Abstract: Ocular toxoplasmosis is the most common cause of retinochoroiditis worldwide in humans. Some studies highlighted the idea that ocular lesions differ according to the route of infection but none of them mimicked the natural route. The current study aimed to investigate the ophthalmic outcomes in congenital and oral routes of infection with Toxoplasma in experimental animals. Mice were divided into three groups; group I: congenital infection, group II: acquired oral infection and group III: non-infected. We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…54 Additionally, because the immune mechanisms between intraperitoneal infection and peroral infection are different, 58 the associated pathologic outcomes are different as well. Some congenital OT models were investigated pathologically, 56,59 and the peroral infection route was reported to cause fewer ocular pathologic changes compared with congenital infection. 59 Thus the route of infection might affect the pathologic outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 Additionally, because the immune mechanisms between intraperitoneal infection and peroral infection are different, 58 the associated pathologic outcomes are different as well. Some congenital OT models were investigated pathologically, 56,59 and the peroral infection route was reported to cause fewer ocular pathologic changes compared with congenital infection. 59 Thus the route of infection might affect the pathologic outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Some congenital OT models were investigated pathologically, 56,59 and the peroral infection route was reported to cause fewer ocular pathologic changes compared with congenital infection. 59 Thus the route of infection might affect the pathologic outcome. Moreover, differences in parasite factors (such as the pathogenicity of T. gondii strains 48,60 and primary parasite load), host factors (such as mouse strain), or clinical stage factors (such as congenital or acquired, primary or recurrent, and acute or chronic) might influence the pathologic findings.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the profile of the structures of retinal layers, such as detachment of the pigmented epithelium from the ONL and irregularities in the placement of retinal layers, have been described in the literature in congenitally infected mice, where ocular abnormalities were more evident than in acquired infection (Ashour et al, 2018). However, the literature lacks studies systematically describing whether the damage found in congenital OT is derived from alterations that occur during the proliferation and differentiation of retinal progenitor cells during development.…”
Section: Congenital Toxoplasmosismentioning
confidence: 99%
“…These changes were noticed in congenitally T. gondii-infected mice, where more extensive eye damage was noted as compared to acquired OT (Ashour et al, 2018). Moreover, congenital T. gondii infection in mice caused structural damage to the retina of infected offspring, including reduced number of cells in the Outer Nuclear Layer (ONL), mild alteration of Müller glial markers and disorganization of nuclear layers (Lahmar et al, 2010(Lahmar et al, , 2014Ashour et al, 2018). Despite the severity of congenital ocular toxoplasmosis and the efforts to establish experimental models to recapitulate the human disease in the laboratory settings, very few studies have successfully detected the parasite (either tachyzoites or cysts) in the retinal tissue per se (Lee et al, 1983;Hay et al, 1984;Lahmar et al, 2010;Dukaczewska et al, 2015).…”
Section: Introductionmentioning
confidence: 99%